An Activatable Polymeric Reporter for Near‐Infrared Fluorescent and Photoacoustic Imaging of Invasive Cancer. Issue 18 (18th March 2020) - Li, Qing; Li, Shenhua; He, Shasha; Chen, Wan; Cheng, Penghui; Zhang, Yan; Miao, Qingqing; Pu, Kanyi
Abstract: Discriminative detection of invasive and noninvasive breast cancers is crucial for their effective treatment and prognosis. However, activatable probes able to do so in vivo are rare. Herein, we report an activatable polymeric reporter (P‐Dex) that specifically turns on near‐infrared (NIR) fluorescent and photoacoustic (PA) signals in response to the urokinase‐type plasminogen activator (uPA) overexpressed in invasive breast cancer. P‐Dex has a renal‐clearable dextran backbone that is linked with a NIR dye caged with an uPA‐cleavable peptide substrate. Such a molecular design allows P‐Dex to passively target tumors, activate NIR fluorescence and PA signals to effectively distinguish invasive MDA‐MB‐231 breast cancer from noninvasive MCF‐7 breast cancer, and ultimately undergo renal clearance to minimize the toxicity potential. Thus, this polymeric reporter holds great promise for the early detection of malignant breast cancer. Abstract : A polymeric NIR fluorescence/photoacoustic probe : An activatable polymeric reporter (P‐Dex ) is designed to produce near‐infrared fluorescence and photoacoustic signals in response to a biomarker (urokinase‐type plasminogen activator) for in vivo imaging of invasive breast cancers. P‐Dex not only has a high sensitivity and specificity towards the cancer biomarker but also undergoes renal clearance in living mice.